Generation of replaceable cryptographic keys from dynamic handwritten signatures - Yip, , WK; Goh, , A; Ngo, , DCL; Teoh, , ABJ (2006)
In this paper, we present a method for generating cryptographic keys that can be replaced if the keys are compromised and without requiring a template signature to be stored. The replaceability of keys is accomplished using iterative inner product of Goh-Ngo [1] Biohash method, which has the effect of re-projecting the biometric into another subspace defined by user token. We also utilized a modified Chang et al [2] Multi-state Discretization (MSD) method to translate the inner products into binary bit-strings. Our experiments indicate encouraging result especially for skilled and random forgery whereby the equal error rates are < 6.7% and similar to 0% respectively, indicating that the keys generated are sufficiently distinguishable from impostor keys.